2019
DOI: 10.1108/mip-01-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori segmentation of elderly internet users: applying PLS-POS

Abstract: Purpose The purpose of this paper is to propose the study of the adoption and use of e-banking by adults over the age of 50, from the theoretical framework based on the unified theory of acceptance and use of technology. Design/methodology/approach After proving the validity of the model, the authors analyse the heterogeneity of these persons by using a structural model-based latent class segmentation called partial least squares prediction-oriented segmentation. Findings The results enable the identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Accordingly, in the case of the Baby Boomer generation, the Baby Boomer birth period varies from country to country (Sudbury-Riley et al, 2015 ). Moreover, although some studies propose the search for heterogeneity within generational cohorts (Rajaobelina et al, 2021 ), other studies have indicated that the differences are not associated with demographic variables such as age but rather psychographic variables such as cognitive age (Arenas-Gaitán et al, 2020 ). In this context, we follow the recent study of Ramírez-Correa et al ( 2019a ) that operationalized the Chilean generations in a digital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the case of the Baby Boomer generation, the Baby Boomer birth period varies from country to country (Sudbury-Riley et al, 2015 ). Moreover, although some studies propose the search for heterogeneity within generational cohorts (Rajaobelina et al, 2021 ), other studies have indicated that the differences are not associated with demographic variables such as age but rather psychographic variables such as cognitive age (Arenas-Gaitán et al, 2020 ). In this context, we follow the recent study of Ramírez-Correa et al ( 2019a ) that operationalized the Chilean generations in a digital setting.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed three significant segments. It is important to check the improvement of the extracted variance (R2) when the segments are considered (Becker et al, 2013;Arenas-Gaitán et al, 2019). In Table 8, when calculating the model with the complete sample (Global), the aggregated R2 of the model is 1.964.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, we applied a latent segmentation method on the basis of structural models which is called PLS-POS (partial least squares predictionoriented segmentation) combining with a conventional structural equation modeling (PLS-SEM). Eventhough PLS (partial least squares) provides general results of statistical analysis, it does not show the characteristics that act as critical segments (Arenas-Gaitán et al, 2019). The PLS-POS enables measuring both the segments and parameters of belonging of the observed variables (Becker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables used are socioeconomic class, the number of people who live with the elder, marital status, educational level, gender, whether the elder lives with his/her partner and if work or not, age, and the use of wearable devices (smartwatch or bracelet). All of these sociodemographic variables are widely used to segment populations in previous studies [ 24 , 26 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this stereotypical image hides a much larger reality. Possibly the elderly is one of the segments with the most significant behavior heterogeneity [ 29 ]. The development of studies on heterogeneity among the elderly, through segmentation, question the current validity of this stereotype [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%